If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 7x + 6b = 0 Reorder the terms: 6b + 7x + 7x = 0 Combine like terms: 7x + 7x = 14x 6b + 14x = 0 Solving 6b + 14x = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-14x' to each side of the equation. 6b + 14x + -14x = 0 + -14x Combine like terms: 14x + -14x = 0 6b + 0 = 0 + -14x 6b = 0 + -14x Remove the zero: 6b = -14x Divide each side by '6'. b = -2.333333333x Simplifying b = -2.333333333x
| 6+w=-12+2w | | -3(y+6)=-45 | | 8a-2b+4-3b+a-3= | | y-9=0.3(x+2) | | 4cos^2x-4cosx-3=3 | | -9x(x+6)=3(x+18) | | a+c=b+c | | -10n+10=-12n | | y-9=0.3(x+9) | | y-7=-3(x-1) | | 3x(4x-8)(x+5)=0 | | (2xlnx-x)/lnx^2=0 | | 13x+4(2x-1)=5(x+2) | | 3a+6b-5a+2b= | | 9b-3b+11=23 | | 8/360=40/x | | 10(x+4)-9(x-3)=8 | | 3(x-7)=x+13 | | 2.27-s/4=2 | | 3(x-7)=x+133 | | 4=2y-3 | | -21x-7=-x+53 | | 8a+2=6a+4 | | 3m+1=m+1 | | X-3=-12x+10 | | x^2+y^2+x+y-96=0 | | 36=-0.5x^2+108 | | 2y+7=-2y-1 | | 4/9/x=12 | | (2x+3y-4)dx+(-4x+y+1)dx=0 | | 7x-3.5=-4x-3.2 | | 2-2x=6-1x |